Surface Marker Expression and Morphological Alterations in Umbilical Cord-Derived MSCs Over Passages 4 to 9: A Flow Cytometry and Microscopic Analysis - Prawitasari, Salindri; Ayu, Dian Respati; Irawan, Risky Chandra Satria; Prabowo, Adam (Stem Cell and Cancer Research (SCCR), 2024)
Background : Umbilical cord-derived mesenchymal stem cells (UC-MSCs) are promising candidates for regenerative medicine due to their high proliferative capacity, multilineage differentiation potential, and low immunogenicity. However, prolonged in vitro expansion may lead to phenotypic drift and morphological changes that could impact their therapeutic efficacy. This study aimed to evaluate the expression of mesenchymal surface markers (CD73, CD90, CD105) and morphological characteristics of UC-MSCs from passage 4 (P4) to passage 9 (P9). Methods: Flow cytometry was employed using the BD Stemflow™ Human MSC Analysis Kit to quantify the expression of both positive and negative surface markers, while morphological assessments were performed via phase-contrast microscopy. Results : The results revealed that UC-MSCs maintained high expression levels of CD73, CD90, and CD105 across all passages, although a slight decline was observed in later passages. Morphological analysis indicated a transition from spindle-shaped, fibroblast-like cells at early passages to more enlarged and flattened cells with signs of senescence at higher passages. Conclusions : These findings suggest that although UC-MSCs retain their phenotypic identity up to P9, subtle morphological and marker expression changes may occur, underscoring the importance of passage selection in therapeutic applications. This study contributes to the optimization of UC-MSC culture protocols for standardized and effective clinical use.